2017
DOI: 10.21608/jappmu.2017.45843
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryopreservation of Buffalo and Bovine Spermatozoa on Sperm DNA Damage and Early Embryonic Development

Abstract: Semen was collected using artificial vagina as per the standard practice from 3 healthy Egyptian buffalo and 3 Holstein Friesian bulls with good body condition, and their age ranged between 4 to 6 yr. Routine semen evaluation was performed. For a better prediction of buffalo and bovine sperm fertility, the first objective was to measure DNA fragmentation in buffalo and bovine bull semen using the alkaline Halo sperm assay. The second objective was to study the influence of cryopreservation process on sperm sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is well‐accepted that assisted reproductive technology, particularly semen cryopreservation and artificial insemination, greatly promotes the animal breeding and production. However, compared with dairy cattle, it was shown that the sperm of buffalo is more susceptible to damage during freezing and thawing process than that of cattle (El‐Regalaty, 2017; Garg et al., 2009; Nair et al., 2006). In the light of the above information, the study was conducted to evaluate the effect of melatonin supplementation in semen extender on frozen‐thawed sperm quality of Thai swamp buffalo.…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐accepted that assisted reproductive technology, particularly semen cryopreservation and artificial insemination, greatly promotes the animal breeding and production. However, compared with dairy cattle, it was shown that the sperm of buffalo is more susceptible to damage during freezing and thawing process than that of cattle (El‐Regalaty, 2017; Garg et al., 2009; Nair et al., 2006). In the light of the above information, the study was conducted to evaluate the effect of melatonin supplementation in semen extender on frozen‐thawed sperm quality of Thai swamp buffalo.…”
Section: Introductionmentioning
confidence: 99%